All Solution‐Based Fabrication of Copper Oxide Thin Film/Cobalt‐Doped Zinc Oxide Nanowire Heterojunctions. Issue 7 (5th April 2016) - Aksoy Akgul, Funda; Akgul, Guvenc; Turan, Rasit; Emrah Unalan, Husnu
Abstract : Versatile and intriguing solution‐based processes are utilized to synthesize nanostructured materials for device applications to reduce material production and device fabrication costs. This study presents results on the fabrication and characterization of copper oxide (CuO) coated cobalt‐doped zinc oxide nanowires (Co‐doped ZnO NWs)‐based heterojunction diodes prepared by a two‐step synthesis route through combined hydrothermal growth and sol–gel spin coating. Highly dense, well‐ordered, undoped, and Co‐doped ZnO NWs were successfully grown by hydrothermal method. Complementary CuO thin films were synthesized by sol–gel method and subsequently coated onto both undoped and Co‐doped ZnO NWs through spin‐coating technique. Enhanced diode properties with a rectification ratio of 10 3 at ±2 V and an ideality factor of n = 2.4 (in dark) were obtained for Co‐doped ZnO NWs‐based heterojunction diodes. The obtained results demonstrated that the investigated heterojunction diode structure fabricated by facile and cost‐effective solution‐based processes can be a promising candidate for the next generation optoelectronic devices.